Sustainable biomass-based filter for high-efficiency PM0.3 filtration - Qingxiang Wang; Zhaoxuan Niu; Wanli Cheng; Ming Yang; Jie Yan; Jiqing Lu; Haijiao Yu; Yiying Yue; Yen Wei; Dong Wang; Shichao Zhang; Bin Ding; et al. (Nature Communications)
Abstract Biomass materials have been widely used in various industries to achieve a carbon-neutral and sustainable society. Here, we show a heterogeneous corn-based precursor strategy that transforms low-value agricultural waste into structural air filters composed of alternating microfibers (2.61 ± 1.11 µm) with grooved surface and nanofibers (0.29 ± 0.18 µm). Utilizing a green solute-solvent system of zein derived from corn and cellulose extracted from corn straw, the process ensures sustainability across raw material sources, fabrication, filtration, and end-of-life degradation. By tailoring relative humidity and incorporating cellulose, an incomplete nonsolvent-induced phase separation is triggered, leading to a corn-based dual-network filter with high filtration performance (>99.99% PM0.3 removal) and low pressure drop (45 Pa). The life cycle assessment demonstrates that the corn-based filter results in lower carbon emissions and environmental impacts than petroleum-based filters. This work provides a promising pathway toward the development of sustainable and disposable filtration materials.